Amalgamation of Quality by Design and Convolution Concept for the Development of Oxcarbazepine Modified Release Granules - Hiral, Koradia (Asian Journal of Pharmaceutics (AJP), 2017)
Introduction: The main objective of this study was to amalgamate quality by design (QbD) concept to develop oxcarbazepine modified release granules with pre-designed qualities. Materials and Methods: Modified release granules of oxcarbazepine were prepared using three different waxes. In this study, modified drug release was considered as quality targeted product profile; drug release at 2, 6, and 12Â h was selected as critical quality attributes, type of wax and amount of wax were the critical material attributes. Results and Discussion: As per QbD, 32 full factorial batches were evaluated for effect on drug release at different time points. The optimized formulation was subjected to X-ray diffraction (XRD) study. The results of XRD showed that the crystal form of the drug remained unaltered after the melt granulation process. The robustness of the optimized formulation was checked by dissolution study considering different pH of dissolution medium, using hydroalcoholic medium and by simulating condition after meal. Based on the in vitro drug dissolution studies in different media, modified drug release is expected from the formulation. The dissolution studies in simulated dissolution media showed insignificance effect of food and combined food and alcohol on drug release. The convolution derived plasma concentration time profile indicated sustained release from modified release granules. From the result, design space was generated, and after implementation of control strategy, the risk factors were below critical level. Conclusion: The use of QbD and convolution approach makes it possible to develop formulation with desired qualities in short time.